Evaluation of crosslinking degree on the integral membrane by using Rice Husk Ash (RHA) / Nurul Atirah Fitriah Mohd Zainuddin, Norin Zamiah Kassim Shaari, Nur Syazwanie Izzati Chik and Fazlena Hamzah - Mohd Zainuddin, Nurul Atirah Fitriah; Kassim Shaari, Norin Zamiah; Chik, Nur Syazwanie Izzati; Hamzah, Fazlena (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Rice husk ash (RHA) is a waste product from the harvesting and processing of rice that contains a high quantity of silica, approximately 95% after combustion. Membrane technology is being developed to remove impurities like heavy metals and dyes as the natural environment deteriorates and water supplies become scarce. Many researchers and developers are now adopting this type of technology. However, it has various drawbacks such as being costly and easily being fouled during the separation process. Therefore, matrix modification of the membrane should be carried out to mitigate these problems. The incorporation of fillers from biomass materials is one of the ways. This research aims to demonstrate the significant effect of incorporating the extracted silica from rice husk ash (RHA) in a polymer-based membrane from a blend of Polyvinyl alcohol/chitosan/polysulfone on the membrane characteristics and antifouling properties. The membranes were prepared by using a phase inversion technique by the incorporation of silica from rice husk ash (RHA) at various concentrations such as 5 wt.%, 7.5 wt.%, and 10 wt.% with a fixed amount of the polymer blends. The results showed that the integral membrane M4 with 10wt.% silica has the best hydrophilicity properties and possesses excellent antifouling properties, which were portrayed through the greater value of pure water flux (PWF) of 20.38 L/m2 .h and the highest flux recovery ratio of 76.32%.